THE INTERDEPENDENCE OF NATIONAL AND UNIVERSAL VALUES IN THE DEVELOPMENT OF SPIRITUAL CULTURE (Scientific journal of the Fergana State University, 2023)
The article deals with the role of spiritual culture in the system of social life, the principles of nationalism and humanity, the importance of mastering spiritual values.